Estudo do produto matricial por meio do método dos mínimos quadrados: uma abordagem destinada ao ensino médio - Souza, Sandro Amorim de (2014)
It has always been a challenge for math teachers to motivate students nowadays, with access to new technologies, this becomes and even greater challenge. One of the strategies that can be utilized in trying to increase the students interest in math classes is the search for application examples for the content seen in class. It s known that this work is not always that simple, making some subjects be seen as plain theory and algebraic, like is the matrix product s case. The present work targets to introduce a real application for the matrix product bringing the Minimum Square Method in Middle School and implementing the GeoGebra software. Furthermore, this proposal s application analysis was performed in a federal institution s Middle School class. Besides the difficulties met during the process, we can say that the reached results were satisfactory, resulting in the proposed work to be achieved.